Midwestern gothic : a collection of horror stories from the American heartland - Thomas, Scott, 1975- (Inkshares, Inc., 2024)
"Close your eyes. Picture open plains, wheat stalks swaying gently in the wind. Picture the quaint Main Street of a one-stoplight town. Picture endless summers on sunny, tranquil lakes. With three provocative novellas, Kill Creek author and Kansas native Scott Thomas takes a hatchet to the idyllic tropes of the American heartland. In The Door in the Field, Thomas follows a quarrelsome construction worker named Rayland Allen whose bad day becomes a far worse night when drinks at an off-the-books establishment deep in the woods set Ray down an unforeseeably bloody path. In The Boy in the Woods, Thomas follows young Eddie Reicher, who lingers a day too long at summer camp as unholy terror creeps in. Something evil has infected the counselors. And Eddie will have to do everything he can, even kill, if he hopes to survive the night. In One Half of a Child's Face, Thomas follows the recently divorced Sienna Franklin. Spying on her son and ex-husband, she notices an odd painting hanging on the wall of an adjacent apartment. Over the course of the next few days, Sienna will watch with growing horror as the children in the apartment building begin to gather before the painting as if called to it. With this collection, Thomas digs his hands into the soil of the American heartland and establishes himself as the master of Midwestern Gothic"--